Actuality of being: Dzogchen and tantric perspectives - Khra-legs-skyabs-mgon (Shogam Publications, 2020)
In this book Traleg Kyabgon Rinpoche elaborates on key aspects of the view, meditation and action of Dzogchen practice and outlines the way in which confusion arises; the notions of self-existing wisdom, primordial purity and non-conceptuality; the four levels of mind; the three ways of resting the mind; the three aspects of energy; authentication of body, speech and mind; and the actualization of the ground; and presents profound practice methods to deepen ones understanding and experience. Compiled from a series of retreats led by Rinpoche, Actuality of Being: Dzogchen and Tantric Perspectives discusses Dzogchen (also known as Maha Ati and the Great Perfection) in relation to the nine yana system. The nine yana system is a set of nine successive steps used as a guide for spiritual growth within the Nyingma tradition of Tibetan Buddhism. Dzogchen, while generally presented within the nine yana system is in fact seen as independent of any system, school of thought or philosophy. Recognised as a complete path within itself, Dzogchen emphasizes the notion of sudden or instantaneous enlightenment, or self-liberation. In Dzogchen practice the beginning and the end are not seen as separate. The very starting point is the end itself. There is no difference between the alpha and omega, in the sense that when you realize Dzogchen, you have not realized anything different from what you already possess. Traleg Kyabgon Rinpoche